Características da pastagem de azevém anual e produção de leite sob diferentes estratégias de manejo - Miguel, Marcolino Frederico; Ribeiro Filho, Henrique Mendonça Nunes; Crestani, Steben; Ramos, Fabiana da Rocha; Teresa, Tereza Cristina Moraes (Pesquisa Agropecuaria Brasileira, 2012)
<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The objective of this work was to assess the effects of the sward structure of Italian ryegrass (<span style="line-height: 115%; font-family: "TimesNewRomanPS-ItalicMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Lolium multiflorum<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">), during the first grazing cycle, on its morphological and bromatological characteristics throughout the growing season, and on the performance of dairy cows. The treatments consisted of two structures obtained as a function of canopy-light interception: high-light interception (HLI) and low-light interception (LLI), with different pre‑<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">grazing heights in the first grazing cycle. Pasture was managed under rotational grazing with a herbage allowance not below 30 kg dry matter (DM) per cow per day. Three grazing cycles, with a grazing interval of 30 days, were evaluated. Pre‑<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">grazing herbage mass was greater (2,240 vs. 1,656 kg ha-1<span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 6pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> <span style="line-height: 115%; font-family: "TimesNewRomanPSMT","serif"; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: TimesNewRomanPSMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">DM), but the proportion of leaf blades was smaller (0.35 vs. 0.43) for HLI swards. Neutral detergent fiber (NDF) content and organic matter digestibility (OMD) were similar between treatments in the first grazing cycle, but in the second and third ones NDF was greater, and OMD lower, for the HLI swards. Milk yields were greater for cows grazing LLI swards (19.4 vs. 21.1 kg per day). Initial grazing with 90% of light interception promotes greater nutritional value in the subsequent cycles.